Comparison of injecting drug users who obtain syringes from pharmacies and syringe exchange programs in Tallinn, Estonia - Talu Ave; Abel-Ollo Katri; Uusküla Anneli; Vorobjov Sigrid; Rüütel Kristi; Des Jarlais Don C (BMC, 2009)
Abstract Background Both syringe exchange programs (SEPs) and pharmacy sales of syringes are available in Estonia, though the current high incidence and high prevalence of HIV among injection drug users (IDUs) in Tallinn, Estonia requires large-scale implementation of additional harm reduction programs as a matter of great urgency. The aims of this report were to compare risk behavior and HIV infection and to assess the prevention needs among IDUs who primarily use pharmacies as their source of sterile syringes with IDUs who primarily use SEPs in Tallinn. Methods A cross-sectional study using respondent-driven sampling was used to recruit 350 IDUs for an interviewer-administered survey and HIV testing. IDUs were categorized into two groups based on their self-reported main source for syringes within the last six months. Odds ratios with 95% CI were used to compare characteristics and risk factors between the groups. Results The main sources of sterile needles for injection drug users were SEP/SEP outreach (59%) and pharmacies (41%). There were no differences in age, age at injection drug use initiation, the main drug used or experiencing overdoses. Those IDUs using pharmacies as a main source of sterile needles had lower odds for being infected with either HIV (AOR 0.54 95% CI 0.33-0.87) or HCV (AOR 0.10 95% CI 0.02-0.50), had close to twice the odds of reporting more than one sexual partner within the previous 12 months (AOR 1.88 95% CI 1.17-3.04) and engaging in casual sexual relationships (AOR 2.09 95% CI 1.24-3.53) in the last six months. Conclusion The data suggest that the pharmacy users were at a less "advanced" stage of their injection career and had lower HIV prevalence than SEP users. This suggests that pharmacies could be utilized as a site for providing additional HIV prevention messages, services for IDUs and in linking IDUs with existing harm reduction services.